A big picture view of precision nutrition: from reductionism to holism - Kwon, Oran (Journal of nutrition and health, 2019)
Purpose: This review describes the historical changes in nutrition philosophy from a reductionist to a holistic approach during the 20th century. Also, the role and efficient use of a holistic approach to precision nutrition are discussed. Results: Over the past century, significant progress has been made in human nutrition research, unraveling fundamental mechanisms of single nutrients on single targets or pathways. This kind of a reductionist approach has helped to save populations from nutrient deficiency diseases and improve associated health outcomes in large parts of the world. However, a new set of nutrition problems, like obesity and diet-related chronic diseases, are growing each year worldwide, increasing the financial burden on the health care system. A linear cause-effect association between single nutrients and a single physiologic effect, is insufficient to solve the complex nutrition-health relationships. Research that involves a more holistic rather than reductionist approach is needed to tackle a new set of nutrition problems. Recent advances in technology, informatics, and statistical methods are enabling an understanding of the diversity of individuals and the complex interactions between foods and human bodies, leading to the concept of “precision nutrition.” Conclusion: The emerging goal of precision nutrition is to provide tailored dietary advice for maintaining health and preventing obesity and diet-related chronic diseases. The parts are already being installed. To grab the complexity, reductionism and holism must be used interdependently. KCI Citation Count: 0